2010
DOI: 10.3748/wjg.v16.i35.4443
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance ofHelicobacter pylori cagAandiceAgenotype status

Abstract: Virulence factors were not common in our cohort. The incidence of factors cagA, iceA1 and iceA2 were very low although variations were noted in different ethnic groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 24 publications
3
13
0
Order By: Relevance
“…We found an association between H. pylori strains harbouring the iceA2 allele in patients with NUD. This behaviour has also been described in Europe, Saudi Arabia, and Turkey [ 34 ]. Several studies suggest an association of the iceA1 variant and PUD and between iceA2 variants with gastritis [ 34 , 35 ].…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…We found an association between H. pylori strains harbouring the iceA2 allele in patients with NUD. This behaviour has also been described in Europe, Saudi Arabia, and Turkey [ 34 ]. Several studies suggest an association of the iceA1 variant and PUD and between iceA2 variants with gastritis [ 34 , 35 ].…”
Section: Discussionsupporting
confidence: 60%
“…This behaviour has also been described in Europe, Saudi Arabia, and Turkey [ 34 ]. Several studies suggest an association of the iceA1 variant and PUD and between iceA2 variants with gastritis [ 34 , 35 ]. However, this association varies among populations; in Brazil, for instance, iceA1 allele is associated with gastritis [ 31 ].…”
Section: Discussionsupporting
confidence: 60%
“…They found an association between H. pylori strains harboring the iceA2 allele in patients with nonulcer disease. This behavior has also been described in Europe, Saudi Arabia, and Turkey [ 12 ]. However, Huang and his colleagues (2016) revealed no significant association between iceA2 and clinical outcomes [ 1 ].…”
Section: Discussionsupporting
confidence: 59%
“…Furthermore, it was shown that adherence to gastric epithelial cells in vitro stimulates iceA1 transcription [ 11 ]. Several studies suggest an association of the iceA1 variant and PUD [ 12 ]. On the other hand, iceA2 has no homology to known genes, and the function of the iceA2 product remains vague in spite of the fact that this allele is associated with asymptomatic gastritis and nonulcer dyspepsia [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…These data are corroborated by the great variability in bacterial load values obtained. In some patients the number of microorganisms in the gastric mucosa was very small and therefore it is unlikely in these cases that the microorganism had an important influence on the patient’s pathology [6,7].…”
Section: Association Between Cag a And Number Of Microorganisms In Tmentioning
confidence: 99%